Formation of a hydrophobic polyiodide complex during cathodic oxidation of iodide in the presence of propylene carbonate in aqueous solutions, and its application to a zinc/iodine redox flow battery. (1st October 2019) - Ito, Shota; Sugimasa, Masatoshi; Toshimitsu, Yuichi; Orita, Akihiro; Kitagawa, Masaki; Sakai, Masanori
Abstract: A polyiodide complex has been newly obtained during the cathodic oxidation of iodide ions (I − ) in the presence of propylene carbonate (PC). This complex demonstrates features of both ionicity and hydrophobicity. The properties and structure of this complex were investigated and discussed in the light of electrochemical investigations, instrumental analyses, and theoretical calculations using quantum chemistry. The oxygen atom of the CO bond in PC was considered to play an essential role in forming this complex, and a large dipole moment structure between I2 and PC was suggested by the theoretical calculations. This PC/I2 structure was considered to play an essential role in enhancing the dissolution rate of I2 films on a cathode and in accelerating the cathodic oxidation of I − . A model for the structure of this complex is demonstrated. A zinc/iodine redox flow battery of an aqueous-based single electrolyte-type was examined as an application of this complex to a battery without a cation-exchange membrane. Over 90% Coulombic efficiency was observed through charge and discharge cycles.